Takagi-sugeno type 1-2 fuzzy linear output controller for two-area load frequency control - Mersadek M.; Nagi F.; Permal N.; Ramasamy A.A.P.; Azwin A. (Academic Press, 2025)
This paper presents a Takagi-Sugeno (T-S) fuzzy type 1?2 controller for load frequency control (LFC). Most of the fuzzy controllers implemented for LFC in the past have Mamdani inference. Mamdani inferences give a fuzzy set that is defuzzified to form an output, whereas the T-S inference doesn't require defuzzification as its output is either constant or 1st order linear polynomial expression of inputs. T-S linear output dependency on its inputs helps it operate at different operating conditions of a dynamic nonlinear system. In this work, a combination of both constant and linear outputs for T-S fuzzy are used to implement a controller for LFC. A two-area tie-line power system is used for demonstration purposes. LFC has gained more importance with the introduction of deregulated renewable energy sources (RES) access to the grid. The proposed controller demonstrates higher stability for almost 30% load variation than its predecessors? fuzzy controllers. ? 2024